The Position of Czechia and Poland in Agri-Food Value Chains - Kohut, Dominik; Vlčková, Jana; Hnát, Pavel, 1981-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This dissertation assesses and compares the position of Czechia and Poland in agri-food global value chains (GVCs). While both countries are EU members with similar geographic and economic profiles, their agri-food sectors differ significantly due to historical and structural factors. The analysis combines GVCs indicators, trade and production data, and firm-level insights to examine integration patterns, value creation, and competitiveness. A central part of the analysis is based on Inter-Country Input-Output (ICIO) tables, which allow for standardized measurement of value-added trade and GVCs participation. Findings show that Czechia is positioned more upstream, specializing in raw and semi-processed goods, with strong dependence on imports of final products. Poland, by contrast, holds a more downstream position, with a diversified production base and strong export performance in processed food. Firm-level analysis further highlights differences in ownership, efficiency, and structure. The study contributes to the limited literature on agri-food GVCs in Central and Eastern Europe and offers insights relevant to trade policy, rural development, and economic resilience.
Vedoucí práce: Jana Vlčková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní ekonomické vztahy [obor disert. práce]; disertace; dissertations